The Dynastic Centre and the Provinces - Duindam, J.; Dabringhaus, S. (Brill, 2014)
The dynastic centre and the provinces were linked by agents and ritual occasions. This book includes contributions by specialists examining these connections in late imperial China, early modern Europe, and the Ottoman empire, suggesting important revisions and an agenda for comparison. This title is available online in its entirety in Open Access
English
Keywords: History; history; Jiaqing Emperor; Ottoman Empire; Qing dynasty